Death of a Liar : Hamish Macbeth #30 - Beaton, M. C. (New York : Grand Central Publishing, 2015)
"Sergeant Hamish Macbeth is alarmed to receive a report from a woman in the small village of Cronish in the Scottish Highlands. She has been brutally attacked and the criminal is on the loose. But upon further investigation, Hamish discovers that she was lying about the crime. So when the same woman calls him back about an intruder, he simply marvels at her compulsion to lie. This time, though, she is telling the truth. Her body is found in her home and Hamish must sort through all of her lies to solve the crime"--.
Keywords: Macbeth, Hamish (Fictitious character) -- Fiction; Police -- Scotland -- Highlands -- Fiction; Murder -- Investigation -- Fiction; FICTION / Mystery & Detective / Traditional British; FICTION / Mystery & Detective / Police Procedural; Mystery fiction